Improvement of Islamic Education Learning Model Based on Scientific Approach in Senior High School - Nurasih Istiqomah (Indonesian Journal of Islamic Studies, 2021)
This study begins with anxiety about the learning process in schools that uses conventional and teacher-centered models, which affect the achievement of student learning outcomes. With the presence of the 2013 curriculum, it is clear that the learning process must be more active with a scientific and learner-centered approach. This is what then made the authors conduct research at SMA Islamiyah Babakan Karangpucung Cilacap to determine the learning process of Islamic Education with a scientific approach. This study aims to analyze: 1) Management of the factual PAI learning model, 2) Management of the hypothetical model of Islamic Education learning model with a scientific approach, 3) Finding the management of Islamic Education learning model that is in accordance with the scientific approach. This research was designed in the form of Research and Development (R & D). Data collection methods used were observation, interviews, and documentation. Meanwhile, to analyze the data using analysis with a phenomenological approach that departs from certain facts or phenomena that occur in the field and then conclusions are drawn. The results showed that: 1) the learning process still uses conventional and teacher-centered learning models. 2) developing a learning model based on a scientific approach. 3) the learning model with a scientific approach is appropriate to be used as an appropriate Islamic Islamic education learning model.